CRITICAL PEDAGOGY IN THE DIGITAL ERA - Agus Syabarrudin; Imamudin imamudin; Marlina Saptariana (JURNAL EDUSCIENCE (JES), 2023)
In the 4.0 industrial revolution, the world of education has taken advantage of developing technology. In this case, pedagogy which is the science of educating, play an important role. Therefore, this study was conducted to find out more about role of pedagogy. This research was conducted through literature review research methods. In fact, in this digital era, there is a gap. Namely that students are more adept at adapting technology compared to educators, this is what makes educators have to study, master, and adapt technology, especially in the teaching and learning process takes place while understanding students in this era. Critical pedagogy will develop and apply critical theoretical concepts in education and cultural studies. Critical pedagogy aims to help students lead meaningful lives by maximizing insight and developing moral sensitivy in applying social conditions in Indonesia and developing their thinking towards open, fair, and free social change. Critical pedagogy has an attempt to reduce the tendency of authoritarian education. Critical pedagogy is also considered to have a profound impact on democratic progress in this country because it can encourage its citizens to think critically, have board insight, make judgements, and take responsibility for their actions.  Keyword: Critical pedagogy, Digital Era, Indonesia. AbstrakPada revolusi industri 4.0, dunia pendidikan telah memanfaatkan teknologi yang berkembang. Dalam hal ini, pedagogik yang merupakan ilmu mendidik pasti ikut berperan penting. Oleh karena itu, penelitian ini dilakukan untuk mengetahui lebih lanjut mengenai peran pedagogik. Penelitian ini dilakukan melalui metode penelitian tinjauan pustaka. Nyatanya, pada era digital ini terdapat kesenjangan, yaitu para peserta didik sudah lebih mahir mengadaptasi teknologi dibandingkan dengan para tenaga pendidik, hal inilah yang membuat tenaga pendidik harus lebih mempelajari, menguasai, dan mengadaptasi teknologi khususnya dalam proses belajar mengajar berlangsung sembari memahami para peserta didik di era ini. Pedagogi kritis akan mengembangkan serta menerapkan konsep teori kritis dalam pendidikan dan studi budaya. Pedagogi kritis bertujuan membantu peserta didik menjalankan hidup yang bermakna dengan memaksimalkan wawasan dan mengembangkan kepekaan moral dalam menerapkan keadaan sosial di Indonesia dan akan mengembangkan pemikirannya terhadap perubahan sosial yang terbuka, adil, dan bebas. Pedagogi kritis memiliki upaya untuk mengurangi kecenderungan pendidikan otoriter. Pedagogi kritis juga dianggap sangat berdampak pada kemajuan berdemokrasi di negara ini karena dapat mendorong warga negaranya untuk berpikir kritis, berwawasan luas, membuat penilaian, dan bertanggung jawab atas tindakannya. Kata Kunci: Pedagogik kritis, Era digital, Indonesia